2020
DOI: 10.1016/j.trechm.2019.07.002
|View full text |Cite
|
Sign up to set email alerts
|

The Structure and Function of DNA G-Quadruplexes

Abstract: Guanine-rich DNA sequences can fold into four-stranded, noncanonical secondary structures called G-quadruplexes (G4s). G4s were initially considered a structural curiosity, but recent evidence suggests their involvement in key genome functions such as transcription, replication, genome stability, and epigenetic regulation, together with numerous connections to cancer biology. Collectively, these advances have stimulated research probing G4 mechanisms and consequent opportunities for therapeutic intervention. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
568
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 639 publications
(622 citation statements)
references
References 127 publications
8
568
0
4
Order By: Relevance
“…The strong stacking interactions between the tetrads lead to a remarkable thermodynamic stability, with the stability of RNA G‐quadruplexes exceeding that of DNA G‐quadruplexes . DNA G‐quadruplexes can be detected in vivo and their fundamental role in telomere maintenance as well as in gene regulation is generally acknowledged . Bioinformatics and in vitro studies suggested the presence of G‐rich putative quadruplex‐forming sites in untranslated regions (UTRs) of mRNAs, as well as in the transcripts of human telomers known as telomeric repeat‐containing RNA.…”
Section: Introductionmentioning
confidence: 99%
“…The strong stacking interactions between the tetrads lead to a remarkable thermodynamic stability, with the stability of RNA G‐quadruplexes exceeding that of DNA G‐quadruplexes . DNA G‐quadruplexes can be detected in vivo and their fundamental role in telomere maintenance as well as in gene regulation is generally acknowledged . Bioinformatics and in vitro studies suggested the presence of G‐rich putative quadruplex‐forming sites in untranslated regions (UTRs) of mRNAs, as well as in the transcripts of human telomers known as telomeric repeat‐containing RNA.…”
Section: Introductionmentioning
confidence: 99%
“…1B) on top of each other, in which the four guanines making up a G-quartets are connected via Hoogsteen pairs (Fig. 1C) [25][26][27][28]. Extensive research indicated that G-quadruplexes were involved in many critical biological processes, including DNA replication [29][30][31][32], telomere regulation [33][34][35][36][37], and RNA translation [38][39][40][41].…”
mentioning
confidence: 99%
“…The minisatellite arrangement originates from the way in which telomerase synthesizes the DNA, in short, and mostly identical motifs, one by one. Several hypotheses consider that such an arrangement is important because it promotes the recognition of telomere specific proteins by homo-and heterodimers [e.g., (Hofr et al, 2009;Visacka et al, 2012)] and for the potential to form G-quadruplexes that may stabilize chromosome ends or serve as substrates for telomere-specific proteins (Spiegel et al, 2020;Tran et al, 2013). Telomere sequences are well conserved through evolution, and large groups of organisms use the grouptypical telomere motif to build their telomere DNA.…”
Section: How Variable Are Telomere Sequences?mentioning
confidence: 99%